2021
DOI: 10.7175/cmi.v15i1.1464
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in Inflammatory Bowel Disease: Prevention and Monitoring Strategies According With Risk Factors

Abstract: Colorectal cancer (CRC) is slightly increased in inflammatory bowel disease (IBD) patients, with roughly a 2.5-fold increase compared to the general population. Clinical features associated to CRC risks are extent and severity of colonic involvement, disease duration, concomitant primary sclerosing cholangitis (PSC) and/or familial history of CRC in first-degree relatives. Colonic Crohn’s disease (CD) and ulcerative colitis (UC) share similar risks when similar colonic extent is affected. Risk stratification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, traditional immunosuppressive drugs suppress the entire immune system, and increase the probability of infection and cancer development 14 . Studies have found that patients with ulcerative colitis are nearly 2.5 times more likely to develop colorectal cancer than the general population 60,61 . Therefore, developing new ulcerative colitis treatments is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional immunosuppressive drugs suppress the entire immune system, and increase the probability of infection and cancer development 14 . Studies have found that patients with ulcerative colitis are nearly 2.5 times more likely to develop colorectal cancer than the general population 60,61 . Therefore, developing new ulcerative colitis treatments is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic colonic inflammation increases the risk of developing colorectal cancer 60, 61 . Therefore, we assessed whether combinational colon-specific immune niche could prevent the development of colitis-associated colorectal cancer in an established azoxymethane/dextran sulfate sodium model of colorectal cancer 62, 63 (Fig.…”
Section: Resultsmentioning
confidence: 99%